2018
DOI: 10.1177/0958305x18802762
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic solar power plant investment optimization model for economic external balance: Model of Turkey

Abstract: Through using a linear optimization model that interprets solar energy and current deficit parameters, investment plans were performed for countries which have current deficit problem of energy source. The specifics of the study are due to the linear optimization model, which reveals the current deficit and solar energy together for the investment strategy. While the model is constituted, without affecting the existed current account, some parameters based on such as profit transfers for foreign investments, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It was demonstrated that 1 GW investment of PV solar energy provides a current deficit reduction annually ranging between 120-210 million dollars, on average 170 million dollars [39]. In line with the same calculation, the wind energy provides a reduction in imported energy annually costing between 188-328 million dollars which is, on average, 270 million dollars.…”
Section: Objective Functionmentioning
confidence: 75%
See 3 more Smart Citations
“…It was demonstrated that 1 GW investment of PV solar energy provides a current deficit reduction annually ranging between 120-210 million dollars, on average 170 million dollars [39]. In line with the same calculation, the wind energy provides a reduction in imported energy annually costing between 188-328 million dollars which is, on average, 270 million dollars.…”
Section: Objective Functionmentioning
confidence: 75%
“…As the conclusion of the model, it was demonstrated that technological learning, electricity market incentives, and liberalization of energy market are important factors. Alagöz et al [39] developed their 2017-2030 PV solar energy investment plan through LP model for the reduction of current deficit in Turkey. The objective of the developed optimization model was to maximize the reduction of energy-based fossil import, and as per the constraints, they created the optimization model considering constraints such as electricity demand of the next period, capital for the investments, the cost of imported RES system due to technological insufficiency, current account balance, total solar energy potential, and solar energy installed power objective.…”
Section: The Literature Of Optimization In Terms Of Res Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…The excessive use of energy represents a negative and irreversible climate acceleration for the planet and the economy, as indicated Alagöz et al [10]. Where they reveal that high economic growth in developing countries requires a certain level of energy, this leads to greater demands on the use of electricity, since living standards rise with the increase in GDP and GDP per capita, thus being one of the most important parameters.…”
Section: Main Discoveriesmentioning
confidence: 97%